Віктор Романовський – видатна постать української архівістики - Мага, І. (Архіви України, 2008)
The article contains the description of life and creative development of V. Romanovskyi, a well-known historian and archivist, his essential contribution to the development of the national archival thought, formation of the centralized archival institutions system of Ukraine.